Soil-Transmitted Helminths (STH) Infection has no Relations with Anemia on Childrenin SDN Barengan, sub-district Teras, Boyolali - Salsabila, Aryanda Widya Tazkagani; Dirgahayu, Paramasari; Randita, Amandha Boy Timor (Nexus Biomedika, 2015)
Background: STH infections with prevalence degree of 28% become a problem in Indonesia societies, especially those who are trapped in low socio-economic level. The infection often affects children because children commonly lack of knowladge about personal sanitation, and their innate immune response has not well developed yet. STH infection can cause deficiencies of calories and protein, it also can cause anemia. An area with high humidity level like sub-district Teras in Boyolali is such a comfortable place for STH to grow rapidly. This study aimed to investigate whether there were any relation between STH infection and anemia on children in SDN Barengan, sub-district Teras, Boyolali. Method: This was an Observational analityc research with cross sectional approach. This research took place in SDN Barengan, sub-district Teras, Boyolali. Sampling technique for this research was undertaken with technique of purposive sampling. It took qualified students that met criterias, from first grade until fifth grade. The data were taken from feces examination by formol ether concentration method, hemoglobin examination by cyanmethemoglobin method, parentsâ socio-economic demographic questionnaire, personal sanitation questionnaire, and foodrecall. The research was obtained as many as 74 research subjects, and analyzed by chi square. Result: The data showed 35 children (47.3%) were positively infected by STH disease and 11 children (14.9%) positively suffer anemia. The analysis of data showed that there was no significant relations between STH infection and anemia, p = 0.431. Analysis of most dominant factor that affects STH infection was bad habbit of barefooted with p = 0.000 (p < 0.05). Meanwhile, anemia disease was mostly caused by lack of protein intake with p = 0.048 (p < 0.05). Conclusion: STH infection has no significant relations for increasing the prevalence of anemia on children in SDN Barengan, sub-district Teras, Boyolali. Keywords: soil-transmitted helminth infection, anemia, primary school children